2015
DOI: 10.1007/s13205-015-0319-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel multiplex PCR method for the detection of virulence-associated genes of Escherichia coli O157:H7 in food

Abstract: Shiga toxin-producing Escherichia coli O157:H7 (E. coli O157:H7) strains are foodborne infectious agents that cause a number of life-threatening diseases, including hemorrhagic colitis (HC) and hemolytic uremic syndrome (HUS). Shiga toxin 1 (stx1), shiga toxin 2 (stx2), or a combination of both are responsible for most clinical symptoms of these diseases. Hence, various diagnostic methods have been developed so far to detect shiga toxins such as cell culture, ELISA, Rapid Latex Agglutination (RPLA) and hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…To ensure food safety, rapid and reliable diagnostic tools are essential for detecting E. coli O157:H7 in different food products. Multiplex real-time polymerase chain reaction (PCR) has emerged as the most attractive alternative to culture-based and immunological-based methods for detecting E. coli O157:H7 (Jinneman, Yoshitomi, & Weagant, 2003;Li, Liu, & Wang, 2017;Tabashsum, Nazneen, Ahsan, Bari, & Yasmin, 2016;Van Giau, Nguyen, Nguyen, Le, & Nguyen, 2016;Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To ensure food safety, rapid and reliable diagnostic tools are essential for detecting E. coli O157:H7 in different food products. Multiplex real-time polymerase chain reaction (PCR) has emerged as the most attractive alternative to culture-based and immunological-based methods for detecting E. coli O157:H7 (Jinneman, Yoshitomi, & Weagant, 2003;Li, Liu, & Wang, 2017;Tabashsum, Nazneen, Ahsan, Bari, & Yasmin, 2016;Van Giau, Nguyen, Nguyen, Le, & Nguyen, 2016;Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, PCR‐based techniques have the potential to allow for rapid and sensitive detection of foodborne pathogens. In addition, many authors have demonstrated the advantages of using multiplex PCR methods (Elizaquível & Aznar ; Singh, Batish, & Grover, ; Van Giau, Nguyen, Nguyen, Le, and Nguyen (). In this study, rapid, reliable, and specific qPCR method was successfully employed to detect E. coli O157 in food by analyzing the two of the major virulence genes and achieved detection limit of less than 10 3 cells/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The strains used for specificity testing are listed in Table 1. For the identification of five food-borne pathogens and the sensitivity of the multiplex PCR assay experiments, the following strains were used: three strains E. coli O157:H7, one produces both Stx1 and Stx2 (NLU), and one produces Stx1 only (NIHE), the last one has Stx2 only (HCMUS), all were obtained from previously worked [37,38], S. aureus ATCC6538, S. enterica ATCC 14028, L. monocytogenes A TCC15313, and V. cholera ATCC 17802. All strains were grown in tryptic soy broth (TSB) or brain heart infusion (Merck, Germany) at37°C for 24 h. The simultaneous enrichment broth (SEB), which used for simultaneous enrichment of five pathogenic bacteria in this study, was described previously by Kobayashi et al [39].Then, the culture broth was used for DNA extraction and subjected to the multiplex PCR assay.…”
Section: Bacterial Strains and Their Cultivationmentioning
confidence: 99%